1996
DOI: 10.1016/s0266-7681(05)80208-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of Scaphotrapeziotrapezoid Fusion for Isolated Idiopathic Arthritis

Abstract: Scaphotrapeziotrapezoid (STT) joint fusion was carried out for pain relief in eight patients with isolated arthritis. Seven patients had satisfactory relief of symptoms. The subjective results were excellent in five, good in two and bad in one patient, who had non-union of the arthrodesis and was also the only patient to develop trapeziometacarpal arthritis. Average grip strength was 0.8 and lateral pinch strength was 0.7 of that in the other hand. There was a very small relative difference in dexterity. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…In a similar study, Ishida and Tsai documented complete pain relief in 58% of the patients in their series [6]. Average wrist motion postoperatively was 115°compared to 124° on the nonoperated side; residual grip strength was 80% of the contralateral side [21]. Average wrist motion postoperatively was 115°compared to 124° on the nonoperated side; residual grip strength was 80% of the contralateral side [21].…”
Section: Surgical Optionsmentioning
confidence: 77%
“…In a similar study, Ishida and Tsai documented complete pain relief in 58% of the patients in their series [6]. Average wrist motion postoperatively was 115°compared to 124° on the nonoperated side; residual grip strength was 80% of the contralateral side [21]. Average wrist motion postoperatively was 115°compared to 124° on the nonoperated side; residual grip strength was 80% of the contralateral side [21].…”
Section: Surgical Optionsmentioning
confidence: 77%
“…Scaphotrapeziotrapezoid arthrodesis, which has historically been considered the solution for this pathology, has shown to yield a high rate of complications that may result in up to 29% of nonunions. 3,8,10,[37][38][39] Watson et al 40 reviewed 800 STT arthrodeses that were performed to treat different pathologies, and revealed that 13.5% of the patients had complications. Because of this, such technique has gradually fallen into oblivion.…”
Section: Discussionmentioning
confidence: 99%
“…atteint surtout les femmes d'âge avancé [4,5,7]. Son traitement chirurgical peut faire appel soit à l'arthrodèse [13,14], soit à la résection du pôle distal du scaphoïde, suivie ou non d'interposition [5,15,16].…”
Section: Discussionunclassified